Implementing Digital Literacy to Foster Citizenship Attitudes among Fifth-Grade Students at Elementary School No. 2 Pelaga - Rika Putri Rachman; Dewa Bagus Sanjaya; I Nengah Suastika (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the Study: This study aims to examine the implementation of digital literacy in fostering citizenship attitudes among fifth-grade elementary school students and to identify the challenges encountered by teachers, school administrators, and parents in supporting the development of responsible digital citizenship. Methodology: This study employed a descriptive qualitative approach. Data were collected through in-depth interviews involving three key informants, namely the fifth-grade teacher, the school principal, and a parent representative. Data were analyzed using the Miles and Huberman qualitative analysis framework, including data reduction, data display, and conclusion drawing. Main Findings: The findings reveal that integrating digital ethics into Pancasila Education, supported by school policies and active parental guidance, effectively strengthened students' ethical awareness, discipline, tolerance, and responsible behavior in digital environments. Nevertheless, implementation was constrained by inadequate school infrastructure, limited parental digital literacy, and inconsistencies between school and home regulations governing students' digital practices. Novelty/Originality of this Study: This study offers a contextual model of digital citizenship development at the elementary school level by emphasizing the integration of digital literacy within Pancasila Education through collaborative engagement among schools, teachers, and families. It extends existing knowledge by highlighting digital literacy as a practical foundation for strengthening citizenship values from an early educational stage.